A 4-item measure of depression and anxiety: validation and standardization of the Patient Health Questionnaire-4 (PHQ-4) in the general population - Löwe, Bernd; Wahl, Inka; Rose, Matthias; Spitzer, Carsten; Glaesmer, Heide; Wingenfeld, Katja; Schneider, Antonius; Brähler, Elmar (Journal of affective disorders, 2010)
The 4-item Patient Health Questionnaire-4 (PHQ-4) is an ultra-brief self-report questionnaire that consists of a 2-item depression scale (PHQ-2) and a 2-item anxiety scale (GAD-2). Given that PHQ-4, PHQ-2, and GAD-2 have not been validated in the general population, this study aimed to investigate their reliability and validity in a large general population sample and to generate normative data.